Síntese e propriedades de sílicas híbridas contendo surfactantes catiônicos - Campos, Ana Flavia Pinheiro de (Universidade Federal de São Carlos, 2015)
The control of pore geometry and pore diameter of silica mesoporous materials is necessary for application of these materials, mainly in industrial process that depends on the shape selectivity. This way, considerable efforts have been devoted to control pore structure of these materials. In this study it has been found the influence of cetyltrialkylammonium and alkyltripropylammonium (CnPr3Br, n = 14-22) surfactants in the formation and properties of mesoporous silicas and subsequently microporous silicas. Regarding the mesoporous silicas synthesized through cetyltrialkylammonium surfactants, it was observed that the silicas pore size increased and the structural ordering decreased as the head group of surfactants increased. In contrast, the increase of lkyltripropylammonium tail resulted in silicas with larger porous diameter and structural ordering. The mesoporous silica with the largest pore diameter (3,60 nm), synthesized with C22Pr3Br surfactant exhibited narrow pore-diameter distribution and a hexagonal organization characteristic of MCM-41 silica. The performance of alkyltripropylammonium surfactant as zeolitic structure directing agents was also investigated. The results showed the formation of a physical mixture between MFI and magadiite structures under different hydrothermal treatment temperatures. Only after addition of tetrapropylammonium cations to reaction mixture containing alkyltripropylammonium cations it was possible to obtain pure MFI structure. However, the presence of alkyltripropylammonium cations had strong influence on the crystals growth and consequently in the form of zeolite crystals obtained.
Keywords: Catálise; Surfactantes; MCM-41; Sílica híbrida; ENGENHARIAS::ENGENHARIA QUIMICA